The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1113/jphysiol.2014.280420
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and muscular dystrophy differentially affect murine pharyngeal muscles in a region‐dependent manner

Abstract: Key pointsr Millions of elderly individuals have dysphagia, a debilitating and life-threatening condition in which the ability to swallow is impaired.r Several muscles surround the three regions of the pharynx, which are essential for proper swallowing, yet the effects of ageing and disease on these muscles are not well understood.r We demonstrate that the fibre size of murine pharyngeal muscles is differentially affected by ageing and muscular dystrophy depending on their location within the pharynx.r Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…Each region and their associated muscles vary in both location and function. We recently reported that muscles within the nasal, oral, and laryngeal regions of the pharynx are differentially affected by aging and disease . Therefore, all histologic studies were analyzed based on pharyngeal localization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each region and their associated muscles vary in both location and function. We recently reported that muscles within the nasal, oral, and laryngeal regions of the pharynx are differentially affected by aging and disease . Therefore, all histologic studies were analyzed based on pharyngeal localization.…”
Section: Resultsmentioning
confidence: 99%
“… Pharyngeal muscles contain a larger number of activated satellite cells than hindlimb muscle. (A): Schematic representation of murine pharyngeal regions shows NP, OP, and LP (modified from Randolph et al ). (B): Hindlimb (tibialis anterior) and pharyngeal muscles were collected at 9 weeks of age from Myf5‐nlacZ mice, sectioned, and incubated with X‐gal to identify β‐gal + nuclei (blue).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of PABPN1 protein are very low in skeletal muscle (15), making biochemical studies of PABPN1 protein interac-tions in this disease-relevant tissue challenging (29). Although several mouse models exist that express PABPN1, they either express native levels of alanine-expanded PABPN1 (33) or do not equally overexpress WT and alanine-expanded PABPN1 (34,35). Thus, we used electroporation into skeletal muscle to allow direct comparison of the proteins that interact with WT PABPN1 and alanine-expanded PABPN1 in skeletal muscle.…”
Section: Electroporation Can Be Used To Express Epitope-tagged Pabpn1mentioning
confidence: 99%